Acute Myeloid Leukemia with Concomitant BCR-ABL and NPM1 Mutations. (11th April 2019) - Mariotti, Benedetta; Meconi, Federico; Palmieri, Raffaele; De Bellis, Eleonora; Lavorgna, Serena; Ottone, Tiziana; Martini, Vincenza; Lo-Coco, Francesco; Cicconi, Laura
Abstract : We present a case report of a patient with acute myeloid leukemia (AML) characterized by the simultaneous presence of nucleophosmin 1 (NPM1) mutation and the breakpoint cluster region-Abelson (BCR-ABL) fusion oncogene. Our findings emphasize the importance of routinely including BCR-ABL in the diagnostic workup of AML in order to offer to the patients the most appropriate risk category and treatment options.